2023
DOI: 10.1080/22221751.2023.2202281
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection rate and disease severity of the BA.5 Omicron SARS-CoV-2 lineage compared to previously circulating variants of concern in the Canary Islands (Spain)

Abstract: The emergence of the Omicron SARS-CoV-2 variant of concern has changed the COVID-19 scenario as this variant is characterized by high transmissibility and immune evasion ability. To evaluate the impact of this variant on the Canary Islands (Spain) population, we determined the reinfection rates and disease severity associated with the Omicron sublineages and the previously circulating variants of concern. We performed a retrospective observational study on 21,745 SARS-CoV-2 viral genomes collected from Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…This study showed that the total reinfection rate varies among different reinfected variants, with the Omicron variant having a significantly higher reinfection rate than other variants. This is consistent with the research results of Ciuffreda [ 30 ], Cohen [ 31 ], and Pulliam JRC et al [ 32 ]. The Omicron variant has a lower protective effect on reinfection compared to other variants, resulting in a significantly higher reinfection rate of the Omicron variant [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that the total reinfection rate varies among different reinfected variants, with the Omicron variant having a significantly higher reinfection rate than other variants. This is consistent with the research results of Ciuffreda [ 30 ], Cohen [ 31 ], and Pulliam JRC et al [ 32 ]. The Omicron variant has a lower protective effect on reinfection compared to other variants, resulting in a significantly higher reinfection rate of the Omicron variant [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…The lower severity of the BA.4/5 variant compared to the BA.1 and the Delta variants was confirmed in the present study. Studies published on the severity of BA.4/5 found no difference, increase or decrease compared to the earlier Omicron variants ( 3 , 24 , 26 , 33 , 35 , 36 ). However, these conflicting results merit further research as do studies regarding quality of life indicators and their correlation with the severity of the SARS-CoV-2 infection ( 37 ).…”
Section: Discussionmentioning
confidence: 89%
“…Although the current bivalent Omicron-containing booster vaccine produced increased anti-SARS-CoV-2 spike protein IgG and neutralizing antibody titers, these effects were lower in KTXRs than in healthy controls. Therefore, although the severity of the Omicron variants is less than that of the previous lineages 34,35 , KTXRs might be more susceptible to Omicron BA.5 and develop more severe disease.…”
Section: Discussionmentioning
confidence: 98%